Impact of anti-TNF agents in postoperative complications in Crohn's disease: a review - Saab,Mansur (2015)
The real impact of biological therapy (anti-TNF agents) in abdominal operations secondary to Crohn's disease is a matter of debate in the international literature. Several studies demonstrated that there can be an increase in postoperative complications in patients previously treated with these agents. On the other hand, the majority of studies published over the last years question this effect, and did not demonstrate any relationship between biologics and outcomes related to surgical postoperative complications. Some meta-analyses were published, with different outcomes and different conclusions. Experimental studies in animals were also recently published, with opposite results, despite similar methodology. In this review, the authors resume all the relevant papers in the international literature with respect to the theme, and demonstrate the heterogeneity of the studies, as well as the disparity of their results and outcomes. The real impact of anti-TNF agents on postoperative complications in Crohn's disease is still controversial, and needs to be better elucidated. Controlled trials must be performed to better address this issue.